Reconfigurable nonlinear response of dielectric and semiconductor metasurfaces - Carletti Luca (De Gruyter, 2021)
Optically resonant dielectric and semiconductor metasurfaces are an emerging and promising area of nanophotonics and light–matter interaction at the nanoscale. Recently, active tuning of the linear response and nonlinear effects of these components has received an increasing amount of interest. However, so far these research directions have remained separated with only few sporadic works that study their combination beginning to appear in the literature. The evolution of nonlinear metasurfaces based on dielectric and semiconductor materials toward reconfigurable and dynamic components could potentially answer the demand of integrated on-chip components that realize essential functionalities such as frequency conversion, active switching, optical isolation, and all-optical routing. This review provides an overview of recent investigations in this field, reviews the main physical phenomena enabling the dynamic control of the nonlinear response and compares the temporal dynamics of the diverse approaches that have been explored so far. Finally, future directions of dynamic nonlinear metasurfaces are outlined.